2012
DOI: 10.3168/jds.2011-5048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduction of milking frequency and supplementation of vitamin E and selenium above requirements on milk yield and composition in Assaf ewes

Abstract: The aim of this research was to study the effect of milking frequency and supplementation with a vitamin-mineral complex above requirements on intake, body weight (BW), and milk yield and composition in high-yielding Assaf ewes. Sixteen lactating Assaf ewes were used in this study, separated into 4 groups of 4 ewes each. Animals in 2 of the groups (control groups) did not receive any extra vitamin-mineral supplement, whereas animals in the other 2 groups (supplement groups) received daily an oral dose of 1g of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
4
9
1
Order By: Relevance
“…Therefore, reduction in plasma Se concentration may be associated with an inflammatory response caused by the reduction in MF when ODM was applied to one of the glands after TDM. Data from the current study previously reported by Pulido et al (2012) showed that SCC increased in the milk from the ODM gland (4.84 vs. 5.14 log units of SCC for TDM and ODM glands, respectively; P < 0.05), which would be compatible with an inflammatory response as reported in other studies (Nudda et al, 2002;Castillo et al, 2008).…”
Section: Plasma Concentrations Of α-Tocopherol and Sesupporting
confidence: 89%
See 4 more Smart Citations
“…Therefore, reduction in plasma Se concentration may be associated with an inflammatory response caused by the reduction in MF when ODM was applied to one of the glands after TDM. Data from the current study previously reported by Pulido et al (2012) showed that SCC increased in the milk from the ODM gland (4.84 vs. 5.14 log units of SCC for TDM and ODM glands, respectively; P < 0.05), which would be compatible with an inflammatory response as reported in other studies (Nudda et al, 2002;Castillo et al, 2008).…”
Section: Plasma Concentrations Of α-Tocopherol and Sesupporting
confidence: 89%
“…Compared with TDM, ODM did not affect milk fat content but decreased fat yield (Pulido et al, 2012). In general, milk FA profile was similar to that observed in earlier studies in Assaf dairy ewes (Gómez-Cortés et al, 2008).…”
Section: Milk Compositionsupporting
confidence: 86%
See 3 more Smart Citations